Strategi Pengembangan Lembaga Pendidikan Islam di Daerah Minoritas Muslim dan Kawasan Elite - Faisol Hakim (FALASIFA : Jurnal Studi Keislaman, 2020)
Islamic educational institutions or islamic boarding school from the very beginning were founded with the principle of a reason approach rather than a hegemony of power and violence, in contrast to outside Islam which leads to spread based on linear fikiq law with just one legal view. Unlike the development of Islam or Islamic boarding schools in Indonesia through a more refined and high appreciation approach to education and Sufism, with that the Indonesian people of Java specifically can accept Islam with the principle of Sendiko Dawuh Gusti, to the Kings of Java at that time, and in line with the philosophy of Java that did not exist one that is contrary to Islam and answers the challenges of the times, discussion of the folklore of Javanese "angi met closed", "ngundungin ing pakerti", "becik ketitik olo ketoro", meaning that no philosophical value of Java is contrary to Islam, it is in common understanding, and therefore it is natural that the thinking and analogy of education and world development education is increasingly intensive in carrying out construcive education for advanced areas and multiple targets, in the scope of the reluctance of the missionaries or preachers of religion to be seen in the elite regions, now the area has become very relevant and in line with the resulting domino effect being more beneficial and comprehensive. From the reference of researchers, there have been many Muslim scholars and intellectuals broadcasting in the style of islamic boarding school, meaning each with a social approach that is not yet formal in the area of ​​Islamic educational institutions or pesantren. Then the need for strong figures in the economy and intellectuals to comb the elite region.